Deconstructing Emotional Labor - Hechanova, Ma. Regina (Archīum Ateneo, 2011)
The study examines emotional labor in the Philippine call center industry. Surveys were administered to 507 Filipino call center agents to test the relationship of the two facets of emotional labor—surface acting and deep acting—with turnover intent. Using the theories of emotional and contextual dissonance, it was hypothesized that the mechanisms underlying the two facets of emotional labor are different. Support was found for the hypotheses that burnout mediates the relationship between surface acting and turnover intent whereas job satisfaction mediates the relationship between deep acting and turnover intent. Based on role identity theory, it was hypothesized that those with greater career commitment would utilize deep more than surface acting. This was supported by the findings. However, results also suggest a direct relationship between career commitment, job satisfaction, and burnout.